2018
DOI: 10.1016/j.nanoen.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the origin of lithium/nickel ions exchange in layered Li(NixMnyCoz)O2 cathode materials

Abstract: In layered LiNixMnyCozO2 cathode material for lithium-ion batteries, the spins of transition metal (TM) ions construct a two-dimensional triangular networks, which can be considered as a simple case of geometrical frustration. By performing neutron powder diffraction experiments and magnetization measurements, we find that long-range magnetic order cannot be established in LiNixMnyCozO2 even at low temperature of 3 K. Remarkably, the frustration parameters of these compounds are estimated to be larger than 30,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 46 publications
2
74
0
Order By: Relevance
“…Consequently, the e g ‐electrons with higher energy lie close to the Fermi level and have a relatively strong hybridization with neighboring oxygen. Although the t 2g ‐electrons are more localized, they can have a small overlap with the oxygen 2 p‐states, consequently resulting in the super‐exchange interaction . The undesirable cation mixing leads to the transfer of TM ions into Li + diffusion channels.…”
Section: Origins Of Surface/interface Structure Degradationmentioning
confidence: 99%
“…Consequently, the e g ‐electrons with higher energy lie close to the Fermi level and have a relatively strong hybridization with neighboring oxygen. Although the t 2g ‐electrons are more localized, they can have a small overlap with the oxygen 2 p‐states, consequently resulting in the super‐exchange interaction . The undesirable cation mixing leads to the transfer of TM ions into Li + diffusion channels.…”
Section: Origins Of Surface/interface Structure Degradationmentioning
confidence: 99%
“…Zheng et al found that these defects benefit the thermal stability for Ni-rich NCM materials, because the Ni in the Li layer would form 180°Ni−O −Ni super exchange chains [17]. Moreover, it can partially relieve the magnetic frustration by forming a stable antiferromagnetic state in hexagonal sublattice with nonmagnetic ions located in centers of the hexagons [18]. Lee et al have proved that a little amount of Ni 2+ ions occupying Li + (3b) sites is not a major obstacle to the diffusion of Li + ions in the lithium layer [19].…”
Section: Introductionmentioning
confidence: 99%
“…When Sb replaces a Ni atom, every oxygen atom connects one Sb atom and two Ni atoms within MO 2 slabs. Considering Sb atom does not have any spin electrons, thus no magnetic frustration can be observed . Similar with LiNiO 2 , NaNiO 2 can be considered as a prominent example of strong geometrically frustrated material as it shows neither spin nor orbital ordering, of which the frustration parameter value is estimated to be 1.8.…”
mentioning
confidence: 99%